Intergovernmental (dis)incentives, free-riding, teacher salaries and teacher pensions - Maria D. Fitzpatrick (W.E. Upjohn Institute for Employment Research, 2015)
In this paper, I document evidence that intergovernmental incentives inherent in public sector defined benefit pension systems distort the amount and timing of income for public school teachers. This intergovernmental incentive stems from the fact that, in many states, local school districts are responsible for setting the compensation that determines the size of pensions, but are not required to make contributions to cover the resulting pension fund liabilities. I use the introduction of a policy that required experience-rating on compensation increases above a certain limit in a differences-in-differences framework to identify whether districts are willing to pay the full costs of their compensation promises. In response to the policy, the size and distribution of compensation changed significantly. On average, public school employees received lower wages largely through the removal of retirement bonuses. However, the design of the policy led some districts to increase compensation, rendering the policy less effective that it might have otherwise been.
Keywords: H75; H72; H77; J26; I21; I28; 330; Intergovernmental Incentives; Teacher Compensation; Teacher Retirement